Factors that shape pregnant women's perceptions regarding the safety of cannabis use during pregnancy - Mohamed A. Satti; Eda G. Reed; Elizabeth S. Wenker; Stephanie L. Mitchell; Jay Schulkin; Michael L. Power; A. Dhanya Mackeen (BMC, 2022)
Abstract Background Cannabis use among pregnant women has increased. We surveyed pregnant women in rural Pennsylvania to examine cannabis use and opinions regarding its safety during pregnancy. We examined associations between challenges of pregnancy (e.g., exhaustion, pain, nausea) and cannabis use. Methods A cross-sectional survey was administered to a convenience sample of English-speaking pregnant women receiving prenatal care at Geisinger, May-June 2019. Principal component analysis (PCA) was used to construct three scores (overwhelmed/exhausted, happy/optimistic, and health worries) based on 10 questions regarding common experiences during pregnancy (e.g., nausea/vomiting, pain, exhaustion, mood). A score based on four questions regarding cannabis safety during pregnancy was also constructed. Results From a maximum of 300 surveys distributed, 284 were completed (95%). Most participants were white (87%), married (49%) or living with a partner (38%), and had private health insurance (62%). Most women indicated it was unsafe to use alcohol and tobacco products during pregnancy (> 90%), but that proportion dropped to 82% and 63% regarding recreational cannabis and medical cannabis, respectively. Only women with prior cannabis use (23% of sample) continued to do so during pregnancy: 57% of women reporting daily cannabis use prior to pregnancy continued to use cannabis during pregnancy with 33% reporting daily use. Two thirds of users during pregnancy indicated they were self-medicating for: nausea (90%), anxiety (70%), insomnia (30%), and pain management (30%). Many (56%) of the women who used cannabis during pregnancy believed it is safe. Younger women and women who were overwhelmed/exhausted or less happy/optimistic were more likely to believe cannabis use is safe. Women valued healthcare provider advice more than advice from family and friends. Study strengths include a high response rate. Weaknesses include self-report and that is was a convenience sample; however, the demographics of the sample were similar to past studies. Conclusion Women with a history of cannabis use, especially daily use, are at risk of continuing during pregnancy and should receive counseling. Younger women and women with greater stressors during pregnancy also are at greater risk. Screening for prior use and for stressors may identify patients that would benefit from enhanced counseling.